Iconography of the Dormition of the Virgin in the 10 th to 12 th Centuries: An Analysis from its Legendary Sources - Salvador González, José María (Eikón / Imago, 2017)
This article seeks to highlight whether and to what extent the medieval iconography of the Dormition of the Virgin reflects the central or peripheral details of three apocryphal texts whose authors are Pseudo-John the Theologian, Archbishop John of Thessaloniki and Pseudo-Joseph of Arimathea. To do this, we will put in direct relation the narrative details of these three apocryphal legends with the characters, gestures, actions and circumstances set forth in the Byzantine and Western representations of this iconographic motif over the 10 th -12 th centuries.